The Found of Causal Conjunction in Kaylnn Bayron “This Wicked Fate” Novel - Komang Sri Anjayani; Ni Wayan Suastini (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Causal conjunctions play a crucial role in building relationships between propositions in literature. This research analyzes the types and functions of causal conjunctions in conveying cause-effect relationships. The study uses data from Kaylnn Bayron's novel